Anion templated formation of pseudorotaxane and rotaxane monolayers on gold from neutral components. - Zhao, L; Davis, J; Mullen, K; Chmielewski, M; Jacobs, R; Brown, A; Beer, P (2009)
The surface covalent attachment of indolocarbazole axles enables anion templation to be exploited in the formation of pseudorotaxane assemblies via the threading of neutral isophthalamide macrocycles from solution. The anion selectivity of this templating process can be monitored by a number of surface spectroscopic methods and shows subtle differences compared to the same process in solution. Though the fluxional and disordered nature of ethylene glycol extended axle adlayers prohibits detectable threading on the surface, rotaxane monolayers can be generated by a preassociation of the components and templating anion in solution. The threaded macrocycles therein can subsequently be released and detected by mass spectrometry by reductive stripping of the axle.